2007
DOI: 10.1074/jbc.m704079200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a C-terminal Transcriptional Activation Domain of ERK5 by Autophosphorylation

Abstract: ERK5 plays a crucial role in many biological processes by regulating transcription. ERK5 has a large C-terminal-half that contains a transcriptional activation domain. However, it has remained unclear how its transcriptional activation activity is regulated. Here, we show that the activated kinase activity of ERK5 is required for the C-terminal-half to enhance the AP-1 activity, and that the activated ERK5 undergoes autophosphorylation on its most C-terminal region. Changing these phosphorylatable threonine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 38 publications
1
103
0
2
Order By: Relevance
“…MEK5 is responsible for the phosphorylation of Erk5 at the TEY microdomain (Zhou et al, 3148 Journal of Cell Science 123 (18) 1995; Nishimoto and Nishida, 2006). In addition, a report indicated that once Erk5 in phosphorylated at the T-PEY-P sites, it is then able to autophosphorylate at residues located in its C-terminal region (Morimoto et al, 2007). We explored the participation of both kinases as the potential Erk5 mitotic kinase.…”
Section: Erk5-and Mek5-independent Phosphorylation Of Erk5 In Mitosismentioning
confidence: 99%
See 2 more Smart Citations
“…MEK5 is responsible for the phosphorylation of Erk5 at the TEY microdomain (Zhou et al, 3148 Journal of Cell Science 123 (18) 1995; Nishimoto and Nishida, 2006). In addition, a report indicated that once Erk5 in phosphorylated at the T-PEY-P sites, it is then able to autophosphorylate at residues located in its C-terminal region (Morimoto et al, 2007). We explored the participation of both kinases as the potential Erk5 mitotic kinase.…”
Section: Erk5-and Mek5-independent Phosphorylation Of Erk5 In Mitosismentioning
confidence: 99%
“…Within this region of Erk5, Morimoto and collaborators (Morimoto et al, 2007) had identified several residues phosphorylated by active Erk5 after transfection of a constitutively activated MEK5 form (MEK5DD). Even though our data excluded MEK5 or Erk5 as the C-terminal mitotic kinases, the possibility that those residues were the targets for such a phosphorylation, due perhaps to a predisposition for being phosphorylated, led us to create specific point-mutants in which those potentially phosphorylated residues were mutated to non-phosphorylatable ones (alanine residues).…”
Section: Multisite Phosphorylation Of Erk5 In Mitosis Occurs In Its Cmentioning
confidence: 99%
See 1 more Smart Citation
“…In cardiac tissue, ERK5 may couple cells electrically and metabolically by phosphorylating the gap-junction protein Cx43 at a key residue for gap junction communication (Cameron et al, 2003). Also, phosphorylated ERK5 regulates gene expression through its C-terminal transcriptional activation domain (Morimoto et al, 2007).…”
Section: Functionmentioning
confidence: 99%
“…The activation of ERK5 occurs via interaction with and dual phosphorylation in its TEY motif by MKK5 (Mody et al, 2003). MKK5 mediated ERK5 activation leads to ERK5 autophosphorylation in its unique C-terminal domain (Morimoto et al, 2007).…”
Section: Descriptionmentioning
confidence: 99%